2005
DOI: 10.1534/genetics.105.042218
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO FUSARIUM OXYSPORUM 1, a Dominant Arabidopsis Disease-Resistance Gene, Is Not Race Specific

Abstract: Arabidopsis thaliana ecotypes differ in their susceptibility to Fusarium wilt diseases. Ecotype Taynuilt-0 (Ty-0) is susceptible to Fusarium oxysporum forma specialis (f.) matthioli whereas Columbia-0 (Col-0) is resistant. Segregation analysis of a cross between Ty-0 and Col-0 revealed six dominant RESISTANCE TO FUSARIUM OXYSPORUM (RFO) loci that significantly contribute to f. matthioli resistance in Col-0 relative to Ty-0. We refer to the locus with the strongest effect as RFO1. Ty-0 plants in which only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
270
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(280 citation statements)
references
References 60 publications
4
270
2
4
Order By: Relevance
“…9) EFR has been identified in the A. thaliana RLK subfamily XII, which also includes FLS2. 7) Another LRR-RLK, ERECTA, and another RLK, WAKL22 (WALL-ASSOCIATED KINASE-LIKE KINASE 22), are involved in resistance to the necrotrophic fungi Plectosphaerella cucumerina 33) and Fusarium oxysporum 34) respectively. AGB1 has also been found to be involved in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) EFR has been identified in the A. thaliana RLK subfamily XII, which also includes FLS2. 7) Another LRR-RLK, ERECTA, and another RLK, WAKL22 (WALL-ASSOCIATED KINASE-LIKE KINASE 22), are involved in resistance to the necrotrophic fungi Plectosphaerella cucumerina 33) and Fusarium oxysporum 34) respectively. AGB1 has also been found to be involved in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…AGB1 has also been found to be involved in these cases. 19,20,[33][34][35] Therefore, AGB1 might be a common component required for some RLK signaling in PTI. Future studies will address this question.…”
Section: Discussionmentioning
confidence: 99%
“…As in most other plant species, resistance to F. oxysporum behaves as a quantitative trait in Arabidopsis (Diener and Ausubel, 2005), but no immunity has been observed in the Arabidopsis gene pool surveyed so far (Berrocal-Lobo and Molina, 2004;Diener and Ausubel, 2005;Edgar et al, 2006). An increased resistance to F. oxysporum in transgenic plants has been associated with increased JA-responsive gene expression, such as the overexpression of defense genes (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…NahG and eds5), but not necessarily in SA signaling (e.g. npr1), show increased F. oxysporum susceptibility Molina, 2004, 2008;Diener and Ausubel, 2005;Dombrecht et al, 2006), these studies have only reported small quantitative increases in resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is variation in the response to F. oxysporum across Arabidopsis ecotypes and the partial resistance of the commonly studied Columbia-0 (Col-0) ecotype is inherited as a quantitative trait (Diener and Ausubel, 2005). One quantitative trait locus contains the atypical resistance gene RESISTANCE TO FUSARIUM OXYSPORUM1 that encodes WALL-ASSOCIATED KINASE-LIKE KINASE22, but how this gene contributes to resistance is currently unknown (Diener and Ausubel, 2005). One possibility discussed by Diener and Ausubel (2005) is that resistance may be at least partially mediated via SA-regulated defenses.…”
mentioning
confidence: 99%